Desarrollo de una guía metodológica para la gerencia de proyectos de construcción de puentes tipo IDU (áreas de integración, alcance, tiempo y costo) : caso Puente Peatonal de la Auto-Norte con calle 192 en Bogotá (2015)
The development of the Methodological Guide for the management of projects of construction of bridges in metallic structure type IDU, developed for the areas of knowledge of Integration, Scope, Time and Cost, applied to the practical case of the pedestrian bridge located in the Auto-North with Calle 192 in Bogotá, contributes in a precise manner to the fulfillment of the requirements established by the Colombian School of Engineering Julio Garavito, particularly in the Projects Unit, to qualify for the Specialization in Development and Integral Project Management title; it also favors the improvement of critical aspects such as deviations in budget and time in IDU pedestrian bridge construction projects, which are executed by the company SAC Estructuras Metálicas SA, in which the engineer Edilson Hernando Martínez fulfills the role of project manager Rodríguez, member of the work team of this Degree Work. The business model of SAC Estructuras Metálicas S.A. consists of participating in tenders, preferably public, of large scale projects and social impact, whose fundamental characteristic is the use of metal structure. The portfolio that manages the company covers all types of projects such as: vehicle and pedestrian metal bridges, buildings and shopping centers, industrial plants, warehouses, decks and special structures for mining and oil, among the most outstanding. They offer services of studies and designs, manufacture, assembly and transport of the metallic structure as well as maintenance, rehabilitation and conservation of existing works. With the awarding of the project, we proceed to fulfill the contracted services until we deliver a high quality final product. To date, the company has made the manufacture and assembly of vehicular and pedestrian bridges in much of the national territory as in the departments of Caquetá, Meta, Córdoba, Huila and Cundinamarca, among others.